Frivolous words on bamboo and silk: The textual criticism of Zheng Xuan (127-200) - Crone, Thomas (Variants and Variance in Classical Textual Cultures: Errors, Innovations, Proliferation, Reception?, 2024)
This chapter discusses the methodological principles of the text-critical work of the Han dynasty scholar Zheng Xuan (127-200). It examines Zheng Xuan's approach in comparison with critics in his immediate historical environment and attempts to reconstruct the basic steps and intentions of his work. It argues that the methodology of Han critics was at a critical stage in its early development, during which underlying principles and concepts were changing from one generation to the next. Outlining Zheng Xuan's view on the history of his texts and his derived conception of textual variation, the chapter further proposes that Zheng Xuan, first and foremost, attempted to recover the original meaning (yi) of his texts but not their initial graphemic and lexical content. His conception of the Urtext remained vague and was informed by his belief that although the language of his texts had continuously changed over the centuries, they nonetheless could accurately convey the intentions and rites of the ancient sages when corrected and read in an appropriate manner.
Created from Fastlane, Scopus look-up